EFFECT OF BALINESE FLUTE INSTRUMENT FOR IMPROVING COGNITIVE FUNCTION IN ELDERLY - Laksmidewi, Anak Agung Ayu Putri; Tertia, Clarissa; Indah, Carolin Tiara Lestari; Suherlim, Richard; Arshinta, Lasta; Mahadewi, Ni Putu Ayu Putri (MNJ (Malang Neurology Journal), 2024)
Background: Cognitive impairment is mostly affected the elderly population which reduces the quality of life for sufferers and their families. The last research showed that listening to Balinese flute instrument music increased cognitive function, especially in the memory domain. However, the study is still limited to small populations. Objective: to determine whether playing the Balinese flute with or without listening to the "Morning Happiness" song affects the cognitive function of elderly. Methods: This experimental study was conducted on healthy geriatric patients above 55 years old with controlled risk factors or no history of any chronic conditions which were divided into 2 groups. The "Morning Happiness" song will be played with Balinese flute instrument in both groups whereas the intervention will add to listen to similar songs. Results: 28 subjects in the intervention group and 20 subjects in the control group. Both groups were comprised of typical gender distribution with an average of 65.08±6.41 years old. Both the intervention and control groups had improved in MoCA-Ina (The Indonesian Version of Montreal Cognitive Assessment) scores, but the intervention group gained a better Z-score (-3.193, p-value 0.001) than the control group (-1.466, p-value 0.143) after procedural. The delayed recall domain also showed significant improvement in both groups with a Z-score of -3.241 (p-value 0.001) in control and -2.30 (p-value 0.026) in intervention group respectively. Interestingly, the attention domain is improved in the control group with a Z-score of -2.142 (p-value 0.032) rather than in intervention group. Conclusion: The overall MoCa-Ina score was significantly higher in interventional subjects than control, specifically in the delayed recall domain.